1994
DOI: 10.1002/prep.19940190608
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition features of ammonium nitrate and its boron mixture under high pressures

Abstract: The kinetics of ammonium nitrate thermal decomposition was studied by the differential thermal analysis in the pressure range from atmospheric to 1.0 GPa. The decomposition under pressure was shown to obey the zero‐order equation with a constant proportional to the initial HNO3 concentration in the sample. The structural transitions in ammonium nitrate were found to affect its exothermic interaction with boron. The mechanism of this phenomenon was interpreted. The experimental data allowed to establish volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Study of AN decomposition is complex and difficult, in part, due to the pivotal role of pressure and reaction products. The melting point of AN rises with increasing system pressure, while the decomposition initiation temperature also rises, albeit slowly . But these facts do not explain the role of pressure in AN explosions.…”
Section: Decomposition Mechanisms Of Anmentioning
confidence: 90%
See 1 more Smart Citation
“…Study of AN decomposition is complex and difficult, in part, due to the pivotal role of pressure and reaction products. The melting point of AN rises with increasing system pressure, while the decomposition initiation temperature also rises, albeit slowly . But these facts do not explain the role of pressure in AN explosions.…”
Section: Decomposition Mechanisms Of Anmentioning
confidence: 90%
“…Oxley et al studied diverse inerting agents and identified CaCO 3 as the most effective inerting additive, however, they were unable to establish a definitive reason for the exceptional effectiveness of CaCO 3 , although they did note that, with this additive, oxygen tends to go to CO 2 and CaO in preference to N 2 O. Varma and Sinha ran tests using 3 mL sealed ampoules, and found that pure AN exploded at 285°C, while 2% CaCO 3 raised it to 312°C, whereas 2% NaCl lowered it to 213°C. They also reported results for 10 other substances.…”
Section: Reactions Involving Additional Substancesmentioning
confidence: 99%
“…(14) has approximately three times higher heat of reaction than one that produces N 2 O according to Eq. (15). Due to its decomposition to N 2 and its high heat of reaction, AN/KCl exhibited a violent exothermic reaction compared with pure AN.…”
Section: Pdsc-msmentioning
confidence: 97%
“…Most of the anion additives were examined in the presence of several different counter ions [2,15]. However, variation of the cation species (Na ?…”
Section: Introductionmentioning
confidence: 99%
“…The thermal decomposition of AN has been widely studied (10)(11)(12)(13)(14)(15)(16)(17) , but a considerably lower number of works on the thermal behavior of PSAN has been reported. A recent study on this subject can be found in Ref.…”
Section: Thermal Behavior Of Solid Mixtures Of Dnam and Psanmentioning
confidence: 99%